Floating charge debenture as security from shari'ah perspective - Mohd Sharoni, Syairazi Muhammad Husni; Hassan, Rusni (IIUM Press, 2018)
Floating charge debenture is one type of security adopted by the Islamic Banks in Malaysia for non-individual customers. For Islamic banks, it is crucial to ensure that all of their banking products and services are SharÊÑah compliant. However, there is no specific ruling from Bank Negara Malaysia on SharÊÑah compliance status of floating charge debenture. Therefore, the purpose of this paper is to determine the soundness of floating charge debenture as security by Islamic banks in Malaysia from the SharÊÑah perspective. This paper adopted a qualitative method that referred to primary and secondary SharÊÑah sources, as well as other related sources such as guidelines of Bank Negara Malaysia and Accounting and Auditing Organization for Islamic Financial Institution. The paper found that it is permissible for an Islamic bank to accept floating charge debenture from non-individual customers as security with certain conditions. This paper suggests that the Bank Negara Malaysia should issue certain resolution related to this issue to arrange related applications in Islamic banks in Malaysia.